AKTIVITAS DIURETIK SELF-NANOEMULSIFYING DRUG DELIVERY SYSTEM (SNEDDS) FUROSEMID - iis wahyuningsih; sugiyanto sugiyanto; Ag Yuswanto; ronny martien (Universitas Muhammadiyah Prof. DR. HAMKA, 2017)
Furosemide is a diuretic having low solubility and low bioavailability thus the diuretic activity is not optimal. The purpose of this study was to determine the effect of furosemide SNEDDS formation to the diuretic activity. SNEDDS was made with a mixture of 66% tween 80, 26% propilene glycol, 8% oleic acid and furosemide 40 mg/mL. A total of 20 test animals were divided into 4 groups, namely the negative control 1 (CMC 0,5% suspension), negativ control 2 (a mixture of tween 80, propilene glycol and oleic acid), furosemid suspension and SNEDDS furosemid. Tests on the diuretic activity is done by measuring the volume of urine released for 6 hours.Furosemide SNEDDS could enhance the diuretic activity of furosemide.